Viability of Paecilomyces fumosoroseus (Wise) conidia stored in palm oil and its derivatives. - Omar, Dzolkhifli; Ibrahim, Yusof; Lok, Chee Ngan (1999)
The viability of Paecilomyces fumosoroseus (Wise) conidia formulated in palm oil and its selected derivatives stored for two and eight at 4C and 25C was evaluated in the laboratory. Vesawit oil gave spore germinations of 95.5% and 88.5% after 2 and 8 weeks respectively and was a better medium for storage of conidia compared with the oleochemical CE 1618 and CE 1897. The POME and PKOME were not suitable for storage as no germination of conidia was obtained. The viability of the conidia stored in Vesawit oil at 4C and 25C showed no significant difference.